The Development Of Character-Based PKn Learning Modules With The Theme Of The Beautiful Diversity In My Country In Class IV SD Asuhan Jaya - Amanda Lestari, Ayu; Dahnial, Irfan (Journal of Elementary School Education, 2023)
This study aims to develop a Character-Based Civics Learning Module with the Theme The Beauty of Diversity in My Country for fourth grade elementary school students on the beautiful material of diversity in my country and to determine the feasibility of a character-based learning module for fourth grade elementary school students on the material of the beauty of diversity in my country. The development model used is the development of R & D Research and Development which uses the Dick and Carey procedural model by using the steps of determining teaching materials to be developed, identifying learning objectives, developing learning strategies, compiling and writing modules and designing conducting formative evaluations revising product development. The subject of this research was SD Asuhan Jaya using a sample of 30 students. The instrument used was a questionnaire consisting of a questionnaire for material experts, language experts, design experts and student response questionnaires. The Character-Based Civics Learning Module with the Theme The Beauty of Diversity in My Country for grade IV elementary school students that has been developed meets the criteria of being suitable for use for fourth grade elementary school students. Feasibility can be seen from the results of the validator, where the results of the module assessment by material experts obtained a value of 88.33%, with a very feasible category, linguists 91.66% in a very feasible category, display experts 90.00% with a very feasible category and response questionnaire students obtained 90.62% with a very interesting category.